Assessment of the non-carcinogenic health risk for the population of the Zakamensky industrial hub associated with the drinking water quality - Irina D. Ulzetueva; Bair O. Gomboev; Natalya B. Gomboeva (Водное хозяйство России: проблемы, технологии, управление)
The basis of the Zakamensky industrial hub was the Dzhida tungsten-molybdenum plant, the city-forming enterprise. In 1996, the enterprise was closed. Nevertheless, rock dumps, drainage mine waters, and a tailing dump continue to this day to create high technogenic loads on the natural environment. In 2014, disturbed lands were reclaimed, while the issues of stopping the discharge of polluted mine waters into water bodies have not yet been resolved.